SERVICE AND CUSTOMER SATISFACTION AT ALFAMART AND WHOLESALE IN MEDAN - Adella Aulia Mukti; Ayu Annisa Suratna; Fakhraini Zahra Afifa; Fitri Agusli; Puji Syahputri (Journal of Mathematics and Scientific Computing With Applications, 2021)
Business in the shopping sector is currently experiencing very rapid progressThe phenomenon of the establishment of various supermarkets in big cities is achallenge for the people who keep up the wholesale. The purpose of this studywas to determine and analyze the differences in customer satisfaction levels inshopping in the minimarket. The methods used were questionnaire methodobservation method and documentation method. The highest value is in theclaim that the place is clean and comfortable, the quality of the layout is cleanand orderly, and the employees have a good view of what Alfamart has. Thehighest value is in the claim that the wholesaler has an affordable product pricefor all sections of the society, so that more consumers go to the Wholesaler tobuy goods in larger quantities.